CERTAIN ISSUES IN THE RECOVERY OF OUTSTANDING CUSTOMS DUTY LIABILITIES - Shadmankulov, Anvar; Ramazonov, Murodjon (Journal of Fundamental Studies, 2026)
This article provides a comprehensive analysis of the system for collecting customs payments in the Republic of Uzbekistan, its role in forming state budget revenues, and the mechanisms for managing customs arrears. It substantiates the financial, protective, regulatory, and control functions performed by customs payments and presents a statistical overview of the composition of revenues transferred to the state budget during 2015–2025. The study examines additional assessments identified after customs clearance, with particular attention to arrears arising from the understatement of customs value, incorrect classification under the HS (Commodity Nomenclature for Foreign Economic Activity) codes, and the unjustified application of customs privileges. It also outlines the current procedural framework for debt recovery, as well as the capabilities and practical challenges associated with the “Debt Accounting Module.” Based on the experiences of Russia and Türkiye, a comparative analysis is conducted with regard to digitalization, centralization, and the enhancement of procedural clarity. The article concludes with specific proposals aimed at improving the efficiency of customs debt recovery, strengthening notification mechanisms for participants in foreign economic activity, and introducing electronic appeal procedures.